The Influence of Natural Environment on the Effectiveness of Guidance and Counseling at Planet Nufo Nature School Rembang - Afifah 'Ainun Ni'mah; Mulawarman; Ali Formen (IJIP : Indonesian Journal of Islamic Psychology, 2024)
This study examines the impact of the natural environment on the effectiveness of guidance and counseling at Nufo Planet School, Rembang. The natural environment surrounding educational institutions is increasingly recognized for its potential influence on student well-being and academic achievement. Employing a qualitative approach, the research utilizes interviews and observations to explore how the natural surroundings at Nufo Planet School contribute to guidance and counseling. The findings indicate that the natural environment plays a significant role in enhancing the effectiveness of counseling sessions, creating a supportive atmosphere for emotional expression and psychological support among students. The implications of these findings underscore the importance of integrating natural elements into educational settings to enhance the effectiveness of counseling interventions.